Manufacturing Dissent: Labor Conflict, Care Work, and the Politicization of Caring - Granberg, Magnus (Nordic Journal of Working Life Studies, 2014)
The article analyzes the phenomenon of “politicization of caring,” observed in studies of nurse labor conflict, in the context of a small-scale episode of conflict at a Swedish hospital ward. Using analytical concepts drawn from work on the role of images of gendered ideal workers in management cultivation of consent, and the method of positioning analysis, it tries to identify the little researched discursive practices involved in the politicization of caring. Analysis of interviews with registered nurses, who took part in a conflict where some of them threatened to resign unless wages were raised and working conditions improved, shows a range of such strategies: including problematizing identities in nursing, expanding the context of caring work, using a discourse of professionalism, and redefining the interpellated image of nursing. Findings indicate that politicization thus has important effects on the gendering of nursing and the viability of neoliberal restructuring of healthcare work.